Aloe vera for prevention of radiation-induced dermatitis: A systematic review and cumulative analysis of randomized controlled trials - Wang, Tingting; Liao, Jian; Zheng, Liying; Zhou, Yi; Jin, Qianru; Wu, Yanjing (Frontiers in Pharmacology, 2022)
Background: Aloe vera has been found to reduce the risk of radiation-induced dermatitis (RID), but the quantitative results from all the relevant studies were not presently available. This study sought to conduct a cumulative analysis so that to better clarify the preventive effects of aloe vera in RID. Methods: Several common database were applied for identifying the eligible randomized controlled trials (RCTs) without language restrictions. The pooled incidence of RID was conducted by the Relative risk (RR) with its 95% confidence interval (CI) through the STATA software under the random-effects model. This systematic review and cumulative analysis were registered on PROSPERO (ID: CRD42022335188). Results: Fourteen RCTs met our predefined inclusion criteria, enrolling 1,572 participants (mean age: 46.5-56 years). The cumulative results revealed that patients pretreated with aloe vera were associated with a significantly lower risk of RID compared to those without aloe vera usage (RR=0.76, 95%CI: 0.67-0.88, P < 0.001; heterogeneity: I2 = 79.8%, P < 0.001). In the subgroup analysis, the pooled incidence of Grade 2-4, Grade 2, and Grade 3 RID was also dramatically lower in the group of aloe vera as compared to the placebo group [RR=0.44 (0.27, 0.74), 0.58 (0.36, 0.94), and 0.27 (0.12, 0.59) in Grade 2-4, Grade 2, and Grade 3, respectively]. However, in regard to Grade 4 RID, the combined RR revealed that the incidence of RID was comparable between aloe vera and the control group (RR = 0.13, 95%CI: 0.02-1.01, P = 0.051; heterogeneity: I2 = 0.0%, P = 0.741). The sensitivity analyses showed that there was no substantial change in the new pooled RR after eliminating anyone of the included study. No significant publication bias was detected in this cumulative analysis. Conclusion: The current cumulative analysis revealed that patients pretreated with aloe vera were less likely to suffer from RID than the controls without using aloe vera. Based on this finding, the prophylactic application of aloe vera might significantly reduce the incidence of RID, especially in Grade 2 and Grade 3 RID. Further large-sample multicenter RCTs are still warranted to confirm these findings and for better clinical application.